A simple fluorescence-based method for detecting total water, methanol, and glycerol in biodiesel - Adegbite, Samson Adeyinka (Kansas State University, 2023)
As biodiesel production and consumption levels rapidly increase around the world, there is a need to monitor the process and the fuel quality. This is essential in order to increase the efficiency of its production and to ensure that products are of high quality and meet regulatory standards. Various factors can influence biodiesel fuel quality due to the nature of the starting material, the production process, and subsequent handling. Additionally, developing an analytical method for quality assessment in biodiesel is of great importance for biodiesel production quality control. This will improve the lifespan of the fuel and the engine, thereby enhancing the economic and environmental sustainability of biodiesel. The whole process of biodiesel analysis could be made more efficient by screening undesirable contaminants in the fuel using a simple, rapid, quicker, fluorescence-based method. These contaminants include methanol, glycerol, water, etc. They have been previously reported to be determined in biodiesel by several spectroscopic methods (like nuclear magnetic resonance and infrared spectroscopy) and chromatographic methods, but these methods require may expensive equipment and sophisticated sample pretreatment procedures. They are also time-consuming and require a high level of technical knowledge. In contrast, fluorescence methods have the main advantage that they can be quickly used to determine whether any or all of these contaminants are present, together, at concentrations above the specified standard level. In this study, Nile red was used as a fluorescent dye for the detection of total water, methanol, and glycerol in biodiesel. The fluorescent probe showed good fluorescence emission and a solvatochromic red shift sufficient to detect polar liquids as they were incorporated into the biodiesel. The calibration curves as well as some figures of merit such as limit of detection, (LOD), and limit of quantification (LOQ) were also reported. The results of this report suggest that the biodiesel used for this experiment incorporates appreciable polar liquids contaminants which may exceed ASTM standards. However, the result needs to be further tested by more selective methods.
Keywords: Biodiesel; Fluorescence; Water; Methanol; Glycerol; Nile red